Green Consumption Behavior and Norms of Adults: A Case from the Mekong River Delta, Vietnam - Phuong, Tran Thi Anh; Nhu Cam, Nguyen Mai (Archives of Business Research, 2022)
This research aims at analysing green consumption behaviour of young consumers from Mekong River Delta, Vietnam by applying the extended theory of planned behaviour (TPB). Data was collected from 342 students in Mekong Delta (MKD) via online platforms. The regression results indicated that four factors affecting students’ green consumer behaviour were Attitude to green consumption, Subjective norms, Environmental awareness, and Perceived behavioural control. Attitude to green consumption was the most impactful factor, whereas Availability of green products did not significantly affect green consumption behaviour. Based on the findings, some managerial implications would be proposed to raise consumers’ awareness of using more environmental-friendly products.